Chemotaxis of a model organism: progress with Dictyostelium. (October 2015) - Nichols, John ME; Veltman, Douwe; Kay, Robert R
Abstract : Model organisms have been key to understanding many core biological processes. Dictyostelium amoebae have the attributes required to perform this role for chemotaxis, and by providing an evolutionary distant reference point to mammalian cells, they allow the central features of chemotaxis to be discerned. Here we highlight progress with Dictyostelium in understanding: pseudopod and bleb driven movement; the role of the actin cytoskeleton; chemotactic signal processing, including how cells adapt to background stimulation, and the controversial role of PIP3. Macropinocytosis and the axenic mutations are raised as potential confounding factors, while the identification of new players through proteomics holds great promise.